Bhagavad-gītā as it is : with the original Sanskrit text, Roman transliteration, English equivalents, translation and elaborate purports - A. C. Bhaktivedanta Swami Prabhupāda, 1896-1977 (The Bhaktivedanta Book Trust, 2022)
One of the most important mystical poems in the Hindu scriptures.